2015
DOI: 10.3390/polym7071346
|View full text |Cite
|
Sign up to set email alerts
|

From Self-Assembled Monolayers to Coatings: Advances in the Synthesis and Nanobio Applications of Polymer Brushes

Abstract: Abstract:In this review, we describe the latest advances in synthesis, characterization, and applications of polymer brushes. Synthetic advances towards well-defined polymer brushes, which meet criteria such as: (i) Efficient and fast grafting, (ii) Applicability on a wide range of substrates; and (iii) Precise control of surface initiator concentration and hence, chain density are discussed. On the characterization end advances in methods for the determination of relevant physical parameters such as surface i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 205 publications
(260 reference statements)
2
111
0
Order By: Relevance
“…Among a number of approaches, a simple but effective and efficient means to bring desired functionality is a copolymerization, i.e ., a polymerization of two or more monomers in a batch to form copolymer chains. Consequential physical and chemical properties can be tuned by incorporating a controlled amount of functional monomers into the copolymer chains where the properties of homopolymers of comonomers are combined . Due to the simplicity and structural predictability, the use of copolymerization for a number of industrial applications can be commonly found.…”
Section: Introductionmentioning
confidence: 99%
“…Among a number of approaches, a simple but effective and efficient means to bring desired functionality is a copolymerization, i.e ., a polymerization of two or more monomers in a batch to form copolymer chains. Consequential physical and chemical properties can be tuned by incorporating a controlled amount of functional monomers into the copolymer chains where the properties of homopolymers of comonomers are combined . Due to the simplicity and structural predictability, the use of copolymerization for a number of industrial applications can be commonly found.…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage of grafting (co)polymers to a substrate is the substrate‐specific grafting chemistry. Dehydration of hydroxy functionality on the (co)polymer is substrate specific (i.e., oxide surfaces), as are other grafting chemistries such as azide‐alkyne cycloaddition, thiol‐ene click, and thiol–gold interactions . Thus, it is highly desirable to fabricate neutral surfaces in a substrate‐independent manner.…”
Section: Substrate Neutralizationmentioning
confidence: 99%
“…However, Cy5-PEG-Au nanoparticles were found to decay in fluorescence intensity dramatically over the course of the study, emitting less than 30 % of the original fluorescence intensity 7 days after fabrication ( figure 4.6(B)). A) brush and (B) mushroom conformations (adapted from Kim et al 2015).…”
Section: Stability Studymentioning
confidence: 99%